CTA concludes the series of 2004 Regional Meetings on S&T - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
CTA in collaboration with the New Partnership for Africa´s Development (NEPAD) and African Technology Policy Studies Network (ATPS), convened the third regional meetings on "Enhancing the Science and Technology Dialogue - Innovation for Development"